Pengaruh Risk Preference dan Tipe Kepribadian Terhadap Pilihan Karir Mahasiswa Akuntansi: Studi pada Mahasiswa S1 dan D4 Akuntansi di Kota Padang - Fitri, Rivi Warensa; Sari, Vita Fitria (Universitas Negeri Padang, 2025)
This study is aimed to determine the effect of risk preferences and differences in personality types of accounting students who choose a career in the public sector and the private sector. This study uses Prospect theory and Carl Jung theory and uses the MBTI (Myers-Briggs Type Indicator) test to measure personality type. The population of this research is accounting students at undergraduate and diploma 4 levels in Padang City, data collection is done by means of surveys distributed directly to accounting students in seven universities in Padang City. This study uses logistic regression and chi-square test. The results showed that there was no significant effect of the risk preference variable on career choices in the public and private sectors, and there were no significant differences in the personality types of accounting students who chose careers in the public and private sectors.